Culturing Maritime Elements in Malay Proverbs: A Preliminary Observation - Ali, Ismail (ASPENSI in Bandung, Indonesia, 2012)
ABSTRACT: Traditionally, the sea and ocean are the source of inspiration for new ideas, aspirations, language, ethnic dignity, and truth. By understanding and acknowledging the roles and functions of these two, i.e. the sea and ocean, in all aspects of life, the ancient Malays have employed maritime elements in their daily life and this has enriched their traditional intellectuality. This article attempts to illustrate the culturing of maritime elements in the Malay proverbs that show the personality, intellectuality, and understanding of the Malay people on the maritime aspects, which at the end enhances the Malay civilization. This preliminary observation also found that the existence and culturing of the maritime-based-proverbs illustrate the close relationship between the traditional Malays and oceans as well as lands. Besides that, the importance of the oceans to the development of Malay civilization in the 18th and 19th centuries has also influenced them in making these proverbs at that time. Finally, the use of proverbs in conversation by the Malay community can avoid misunderstandings and strengthen the bond among them. KEY WORDS: Maritime culture, Malay proverbs, history of maritime, Malay language, and dignity of nation.Â About the Author: Assoc. Prof. Dr. Ismail Ali is a Senior Lecturer at the History Program, School of Social Sciences UMS (Malaysia University of Sabah), Beg Berkunci 2073, 88999 Kota Kinabalu, Sabah, Malaysia. He can be reached at: ismailrc@ums.edu.myHow to cite this article? Ali, Ismail. (2012). âCulturing Maritime Elements in Malay Proverbs: A Preliminary Observationâ in TAWARIKH: International Journal for Historical Studies, Vol.4(1) October, pp.21-36. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (August 4, 2012); Revised (September 7, 2012); and Published (October 28, 2012).